Evaluace přírodních ohrožení glaciálního jezera Imja, Nepál - Kroczek, Tomáš (Univerzita Karlova, Přírodovědecká fakulta, 2019)
Current dynamic of global climate change is the trigger of new natural processes such as glacial lake outburst floods. One example is lake Imja located in the hinterland of Mt. Everest. Outburst of lake Imja would have undoubtedly negative impact on financial and cultural climate of attached area. This diploma thesis is focusing on the various factors and its imapct on the stability of moraine. The main aim of this thesis is to evaluate possibility of impact of rockfall into the lake, to monitor the development of its expansion in comparison with growing temperatures in last 60 years and also to assess the development of morphology of moraine containing dead ice. The results of the thesis indicate accelerating expansion of the lake at the expense of the Imja and Lhotse Shar glaciers, for which the rising means of temperatures of the months in the warm half of the year are particularly important. The results also show that there is no risk of producing wave after impact of rockfall into the lake, as the lateral moraines are sufficiently high to protect the lake. The crucial factor for the stability of the moraine dam is the melting of dead ice in its core, where new and new thermokarst lakes are forming on the surface of the moraine and a seepage through the moraine in its southwestern part has also. Globální klimatická změna přináší mnoho fenoménů, kdy jedním z nich je nepochybně možnost vzniku povodňových vln z nově tvořených ledovcových jezer. Jedním z těchto jezer je také nepálské jezero Imja ležící nedaleko nejvyššího světového vrcholu Mt. Everest a v případě jeho protržení či přelití by došlo k velkým finančním i kulturním ztrátám. Tato diplomová práce se zabývá právě vybranými faktory, které mohou stabilitu morény, jež jezero hradí, ovlivnit. Hlavním cílem práce je evaluace možnosti dopadu skalního řícení do jezera, dále sledování vývoje jeho expanze v posledních letech v souvislosti s vývojem teplot, a také hodnocení vývoje morfologie hradící morény obsahující mrtvý led. Výsledky práce naznačují stále ...